PERMANÊNCIA AO RELENTO E SOMBRA EM NOVILHAS PANTANEIRA E GIROLANDO NAS DIFERENTES ESTAÇÕES DO ANO - LIMA, P. G. L.; FERREIRA, R. C.; MARTINEZ, D. V. S.; FURTADO, A. C.; SALLA, L. E.; OLIVEIRA, M. V. M. (ANAIS DO ENIC, 2016)
-